Improving the Protective Features of Personal Protective Equipment To Ensure Labor Safety of Workers - O.M. Yoldosheva; Hamidullayev Fathulla; Sobirov Sarvar (European Journal of Life Safety and Stability (2660-9630), 2023)
The article provides information on improving the protective properties of personal protective equipment in order to ensure the safety of workers.